Effect of incorporating Lippia javanica (Zumbani) on physical, nutritional, microbiological, and sensory properties of instant soup mix powder - Benhura, Chakare; Mpofu, Shirley; Nyakudya, Elijah (The North African Journal of Food and Nutrition Research, 2024)
Background: Lippia javanica (commonly known as Zumbani) is a nutrients-rich plant with various pharmacological characteristics, including antioxidant, anti-cancer, anti-diabetic, anti-microbial, and bio-pesticidal effects, making it a valuable addition to consumer products. Aims: The aim of the study was to evaluate the effect of incorporating Lippia javanica powder into Instant Soup Mix (ISM) powder on its functional, nutritional, microbiological, and sensory properties. Methods: Four (4) 100 g treatment formulations were prepared using a constant base of 70 g Lippia javanica powder blended with corn flour in varying proportions: 0:70 g (zum–0), 2:68 g (zum–2), 5:65 g (zum–5), and 10:60 g (zum–10), while maintaining all other ingredients constant. Results: The incorporation of Lippia javanica significantly reduced the bulk density of the ISM Powder (p = 0.0098), with values ranging from 0.67 to 0.69 g/mL. Water absorption capacity (WAC) and fat content decreased as the proportion of Lippia javanica increased. Conversely, ISM Powders containing Lippia javanica powder exhibited significantly higher levels of ash, protein, crude fiber, calcium, compared to the control (zum-0). Among the samples, zum–10 displayed the highest content of total phenolic compounds and achieved the highest sensory acceptability scores. Microbiological analysis revealed no bacterial presence in any of the treatments. Conclusion: The inclusion of Lippia javanica powder enhanced the functional, nutritional, and sensory properties of the ISM powders. Sample zum–10 demonstrated superior nutritional value, functional characteristics, and consumer acceptability, making it the most recommended formulation for potential use. Keywords: Lippia javanica, instant mix soup powder, physico-chemical, sensory properties.